2016
DOI: 10.1038/srep38349
|View full text |Cite
|
Sign up to set email alerts
|

Solving the second-order free rider problem in a public goods game: An experiment using a leader support system

Abstract: Punishment of non-cooperators—free riders—can lead to high cooperation in public goods games (PGG). However, second-order free riders, who do not pay punishment costs, reduce the effectiveness of punishment. Here we introduce a “leader support system,” in which one group leader can freely punish group followers using capital pooled through the support of group followers. In our experiment, participants engage in three stages repeatedly: a PGG stage in which followers decide to cooperate for their group; a supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 30 publications
0
13
1
1
Order By: Relevance
“…In larger-scale societies, it can be effective to establish systems other than peer reward and punishment. The pool punishment system and/or the leader support system are important candidates for solving the problem [27][28][29][30][31][32] . The limitations of peer reward and punishment emphasize the importance of investigation into how these systems emerge and are maintained.…”
Section: Discussionmentioning
confidence: 99%
“…In larger-scale societies, it can be effective to establish systems other than peer reward and punishment. The pool punishment system and/or the leader support system are important candidates for solving the problem [27][28][29][30][31][32] . The limitations of peer reward and punishment emphasize the importance of investigation into how these systems emerge and are maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ozono et al . 25 conducted an experiment in which the pool punishment system was governed by a participant and he/she could freely punish group members. The authors found that some governors of the system punished both first- and second-order free riders spontaneously and the group resulted in high cooperation, but other governors punished only nonsupporters and received a certain benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, a punishment system was governed by a specific governor or a few governors of the group, such as headmen in villages, lords of manors, or kings of nations. They could obtain the surplus, and thus, might choose more profitable punishment system for themselves 25 . Therefore, analysis of the surplus has implications for institutional choice by governors.…”
Section: Introductionmentioning
confidence: 99%
“…In this line, different studies have explored how individuals indeed implement institutions of this type, if offered such possibility. The credible threat of this institution sanctioning opportunistic behavior at the end of the day enhances individual cooperation, which in turn has positive effects on group cooperation [33,34]. This effect is even more pronounced with the option of counter-punishment [35].…”
Section: Pool Punishmentmentioning
confidence: 99%